Interplane corrugations in the quasi-one-dimensional Fermi surface sections of kappa-(BEDT-TTF)(2)Cu(SCN)(2) - Rzepniewski, E; Edwards, R; Schrama, J; Ardavan, A; Singleton, J; Kurmoo, M; Day, P (2001)
We identify two interplane corrugations in the quasi-one-dimensional Fermi surface sections of the organic superconductor kappa-(BEDT-TTF)(2)Cu(SCN)(2). The warping directions are 17.3 degrees and -19.4 degrees relative to the crystal a* axis.